Usage of gold mine tailings based geopolymer on Cu2+ adsorption from water - Demir, Funda; Derun, Emek Moroydor (SAGE PUBLICATIONS INC, 2019)
In todays world, heavy metal pollution is one of the major problems. Various methods have been developed for the removal of pollution caused by heavy metals. However, adsorption is the most advantageous process among these methods. Mining waste is another source of pollution. The evaluation of these wastes will both solve the storage problems and prevent environmental pollution. In this study, Bergama gold mine wastes were evaluated and used in geopolymer production. Alkaline fusion method was used for geopolymer synthesis in the experimental process. The obtained geopolymer sample was suitable for adsorption in terms of porosity and surface area and was used in the adsorption of Cu2+. According to the results of the studies, the surface area of the gold mine waste increased from 3.845 m(2)/g to 74.916 m(2)/g. Adsorption studies were carried out at different parameters such as geopolymer dosage, contact time, temperature and initial concentration. Also, isotherm and kinetic studies were applied. Cu2+ adsorption is suitable for the Langmuir isotherm model (R-2 = 1) and the Pseudo-second order kinetic model (R-2 = 0.997).
Keywords: Geopolymer; gold mine tailings; adsorption; heavy metals; HEAVY-METAL ADSORPTION; FLY-ASH; REMOVAL; METAKAOLIN; ISOTHERMS; KINETICS; SORPTION; SILICA; Chemistry